The Future Is Ahead: Can Younger Generation Invests Wisely? - Adirama, Kelvin Fitriyan; Prapanca, Detak; Sari, Herlinda Maya Kumala (Journal of Economics Education and Entrepreneurship, 2025)
This study aims to analyze the influence of risk tolerance, overconfidence, and social media on Generation Z’s investment decisions in Sidoarjo City. The research employs a quantitative method with a data analysis approach. The data used consists of primary data collected through questionnaires filled out by 96 respondents and secondary data obtained from articles and books. In this study, data processing is conducted using SmartPLS software. The analysis techniques applied include the Convergent Validity Test, Reliability Test, Discriminant Validity Test, R-Square Test, and Hypothesis Test. The research findings indicate that risk tolerance significantly affects investment decisions, meaning that individuals with higher risk tolerance are more likely to invest. Additionally, overconfidence is found to have a significant impact, showing that individuals who are overly confident in their decision-making tend to be more active in investment. Lastly, social media plays a crucial role in shaping Generation Z’s investment decisions, as information circulating on various social media platforms influences their mindset and confidence in investing.